Program ECO-HASUPA: Edukasi Pengelolaan Sampah dan Skrining Kesehatan di Kelurahan Pahandut Seberang, Palangka Raya: ECO-HASUPA Program: Waste Management Education and Health Screening in Pahandut Seberang Village, Palangka Raya - Akmal, Rizqy Fajar Syaikhul; Azzahrah, Khairunnisa; Yuliani, Ni Nyoman Sri; Rahman, Raffi Maulana; Mujio, Nadiah Romadhona Putri Erwan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Pahandut Seberang is a residential area vulnerable to flooding due to its proximity to the Kahayan River. The residents’ habit of disposing of waste directly beneath their houses or into the river has resulted in waste accumulation and blockage of water flow, consequently leading to flooding. These floods have submerged many houses and increased the health risk among the population. In response, the Community Service Team from the Student Executive Board (BEM) of the Faculty of Medicine conducted educational activities on waste management and health screening. The activity was attended by 150 residents. The results indicated an improvement in the community’s knowledge of waste management following the educational session, and the majority of health screening results were within normal limits.